Influence Of Potassium Hyaluronate On The Change Of Phospholipase Activity And State Of The Membranes Of Damaged Somatic Nerves Of Rats - V. V. REVIN; M. V. ISAKINA; S. I. PINYAEV; N. V. REVINA; A. A. MOROZOVA (International Journal of Pharma and Bio Sciences, 2015)
It has been established that nerve injury is accompanied by an increase in the content of lysophospholipids and an increased activity both Ca2 + - dependent and Ca2 + - independent phospholipase A2. The introduction of the drug enhances the regenerative processes in damaged nerve that is manifested in the restoration of orderliness of the membranes of nerve fibers, as well as in the reduction of lysophospholipids and activity of Ca2 + - dependent phospholipase A2. However, using the potassium hyaluronate does not lead to changes in the activity of Ca2 + - independent phospholipase A2 that likely indicates that Ca2+ - independent phospholipase A2 is not involved in the mechanism of nerve regeneration. Thus, it can be assumed that the acceleration of regeneration processes in damaged nerve conductor under the action of potassium hyaluronate is likely mediated by the functioning of Ca2+ - dependent phospholipase A2.